Leveraging Hyperforce for Scalable and Secure Multi-Cloud Solutions: An Architectural and Implementation Guide - Chary, Divya (International Journal of Strategic Management, 2024)
Purpose: In today’s fast-paced digital world, businesses are turning to multi-cloud strategies to boost their performance, flexibility, and resilience. This paper aims to provide a straightforward guide on leveraging Salesforce’s Hyperforce in a multi-cloud environment. Hyperforce is designed to work with major public cloud providers, offering unmatched scalability, data residency compliance, and efficiency. The primary objective is to help IT professionals and decision-makers fully leverage Hyperforce in a multi-cloud strategy to drive digital transformation and maintain competitiveness. Methodology: This paper explores the key aspects necessary for a successful Hyperforce and multi-cloud setup, including architectural design, implementation steps, data management, security, performance optimization, and cost management. Through a combination of clear technical insights and real-world examples, the paper illustrates the challenges and best practices associated with implementing Hyperforce in a multi-cloud environment. Findings: By spreading workloads across different cloud platforms, companies can enhance redundancy, avoid vendor lock-in, and optimize resource utilization. The paper identifies critical areas such as architectural design, security, and cost management that are essential for successful multi-cloud adoption using Hyperforce. Additionally, the paper delves into emerging trends and future innovations in the multi-cloud space, providing insights into the evolving landscape and what lies ahead for Hyperforce. Unique Contribution to Theory, Practice and Policy: The paper recommends that IT professionals and decision-makers focus on fully understanding and utilizing Hyperforce’s capabilities within a multi-cloud strategy. This involves following best practices in architectural design, implementation, data management, and security to maximize the benefits of Hyperforce. The insights and tools provided in this paper are intended to equip organizations with the knowledge necessary to effectively implement Hyperforce and drive their digital transformation efforts forward.